Modulation of the Ras/MAPK signalling pathway by the redox function of selenoproteins in Drosophila melanogaster. - Morey, M.; Serras, F.; Baguna, J.; Hafen, E.; Corominas, M. (Developmental Biology, 2001)
Modulation of reactive oxygen species (ROS) plays a key role in signal transduction pathways. Selenoproteins act controlling the redox balance of the cell. We have studied how the alteration of the redox balance caused by patufet (selD(ptuf)), a null mutation in the Drosophila melanogaster selenophosphate synthetase 1 (sps1) gene, which codes for the SelD enzyme of the selenoprotein biosynthesis, affects the Ras/MAPK signalling pathway. The selD(ptuf) mutation dominantly suppresses the phenotypes in the eye and the wing caused by hyperactivation of the Ras/MAPK cassette and the activated forms of the Drosophila EGF receptor (DER) and Sevenless (Sev) receptor tyrosine kinases (RTKs), which signal in the eye and wing, respectively. No dominant interaction is observed with sensitized conditions in the Wnt, Notch, Insulin-Pi3K, and DPP signalling pathways. Our current hypothesis is that selenoproteins selectively modulate the Ras/MAPK signalling pathway through their antioxidant function. This is further supported by the fact that a selenoprotein-independent increase in ROS caused by the catalase amorphic Cat(n1) allele also reduces Ras/MAPK signalling. Here, we present the first evidence for the role of intracellular redox environment in signalling pathways in Drosophila as a whole organism.